Hydrogen storage in MgH2 catalyzed by Fe nanoparticles and hollow silica spheres - Saeid, Mohammed Faraj; Abdulkadir, Bashir Abubakar; M., Ismail; Herma Dina, Setiabudi (Elsevier, 2025)
Hydrogen is a promising clean energy carrier, but its practical use is limited by storage challenges. Solid-state storage, particularly using magnesium hydride (MgH2), offers high capacity, though its application is hindered by high decomposition temperatures and slow dehydrogenation kinetics. To increase the storage capacities of MgH2, this study explored the influence of iron (Fe) doped on hollow silica spheres (HSS). Different amount of Fe was doped into the HSS and characterized using different physicochemical characterization techniques. The results show that Fe was successfully incorporated into the MgH2, with the 7 wt% Fe-HSS sample (7Fe-HSS) exhibiting the most significant improvements. The onset dehydrogenation temperature of pure MgH2 was 420 °C, while ball-milled MgH2 exhibited a reduced onset temperature of 350 °C. MgH2 doped with 3 wt%, 5 wt%, 7 wt%, and 10 wt% Fe-HSS showed onset temperatures of 359 °C, 345 °C, 320 °C, and 335 °C, respectively. The MgH2 doped with Fe nanoparticles, exhibited a similar onset dehydrogenation temperature of 320 °C. The 7Fe-HSS sample decreased the dehydrogenation temperature by 105 °C compared to pure MgH2 and by 30 °C compared to ball-milled MgH2. In terms of hydrogen absorption, the 7Fe-HSS composite absorbed 6.09 wt% H2 in 2 min at 320 °C, compared to 4.66 wt% for ball-milled MgH2, 4.49 wt% for MgH2-HSS, and 4.45 wt% for MgH2-Fe nanoparticles. Over 60 min, the 7Fe-HSS sample desorbed 4.85 wt% H2 at 320 °C, significantly higher than the 0.4 wt% desorbed by ball-milled MgH2, 3.37 wt% by MgH2-HSS, and 4.23 wt% by MgH2-Fe nanoparticles. The hydrogen absorption capacities at 20 min for MgH2-Fe nanoparticles, MgH2-HSS, 3 wt%, 5 wt%, 7 wt%, and 10 wt% Fe-HSS were 4.45 wt%, 4.49 wt%, 4.74 wt%, 5.24 wt%, 6.09 wt%, and 5.17 wt%, respectively. The 7Fe-HSS composite exhibited the highest absorption and desorption rates, with a capacity of 6.09 wt% in 2 min. Additionally, the desorption capacity for the MgH2-Fe nanoparticles, MgH2-HSS, 3 wt%, 5 wt%, 7 wt%, and 10 wt% Fe-HSS samples at 60 min was 4.23 wt%, 3.37 wt%, 4.93 wt%, 5.4 wt%, 4.85 wt%, and 5.27 wt%, respectively, compared to 0.39 wt% for pure ball-milled MgH2. These findings suggest that 7 wt% Fe-HSS is the optimal doping rate for enhancing both hydrogen capacity and desorption kinetics, while higher doping rate, such as 10 wt%, result in decreased storage capacity due to the dead weight of the Fe-HSS. The activation energy for hydrogen desorption was also reduced in all doped samples, with 7Fe-HSS composite showing the lowest value (115 kJ/mol). Furthermore, as compared with pristine MgH2, the 7Fe-HSS has lowered the change in enthalpy by 58.4 kJ/mol. The 7Fe-HSS exhibited five cycles of hy/dehydrogenation, confirming the good cyclability of the synthesized sample. Additional analysis by XRD showed the formation of FeSi2, which indicates the coordination between Fe with the silicon in HSS. It is anticipated that this coordination retains the Fe with HSS, which stops the accumulation of Fe during absorption/desorption. These afford a favourable atmosphere to increase the sorption capacities of MgH2.